2016
DOI: 10.1021/jacs.6b02877
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophile-Assisted Alkene Activation: Olefins Alone Are Often Incompetent

Abstract: Emerging work on organocatalytic enantioselective halocyclizations naturally draws on conditions where both new bonds must be formed under delicate control, the reaction regime where the concerted nature of the AdE3 mechanism is of greatest importance. Without assistance, many simple alkene substrates react slowly or not at all with conventional halenium donors under synthetically relevant reaction conditions. As demonstrated earlier by Shilov, Cambie, Williams, Fahey, and others, alkenes can undergo a concert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
94
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(101 citation statements)
references
References 40 publications
5
94
0
1
Order By: Relevance
“…34 Indeed, the entire spectrum of Ad type reactions from Ad E 2 to Ad N 2 (electrophile initiated, nucleophile initiated, and of course, synchronous in between) is treated in many advanced textbooks on physical organic chemistry. 35,36 …”
Section: Resultsmentioning
confidence: 99%
“…34 Indeed, the entire spectrum of Ad type reactions from Ad E 2 to Ad N 2 (electrophile initiated, nucleophile initiated, and of course, synchronous in between) is treated in many advanced textbooks on physical organic chemistry. 35,36 …”
Section: Resultsmentioning
confidence: 99%
“…[3,4] Although little is known about the thiophilicity versus carbophilicity of boron reagents in synthesis, such knowledge would facilitate the development of thioboration reactions by indicating when B–S σ bonds are necessary and when such bonds can be avoided, aiming instead for previously unknown carbophilic activation of the C–C π bond by boron with simultaneous attack by sulfur via an Ad E 3 or Ad E 2 reaction mechanism (Figure 1b). [5,6] Herein the first formal thioboration of C–C π bonds is reported, concurrently developing fundamental knowledge about guiding principles of relative carbophilicity and thiophilicity. The experiments were motivated by a broader study on gold-catalyzed and catalyst-free oxyboration and aminoboration (B–O and B–N addition) reactions in our research group.…”
mentioning
confidence: 99%
“…Treatment of diphenylacetylene 16, which is the no-sulfur analogue of substrate 1b, under the otherwise standard thioboration conditions resulted in no reaction by 1 H (>95% 16 remaining using mesitylene as an internal standard) or 11 B NMR spectroscopy (only signal detected at δ = 28.6 ppm, corresponding to unreacted ClBcat) in 4 h. This demonstrated that chloroboration product 17 did not form, and thus is an unlikely operative pathway in this thioboration reaction. On the basis of these mechanistic experiments, a role for boron as a carbophilic Lewis acid in this cyclization is proposed, plausibly through an Ad E 2/Ad E 3 mechanism [5,6] (Scheme 2, bottom). Subsequent attack by the sulfur via transition state 13 generates sulfonium intermediate 12.…”
Section: Mechanistic Studies: Boron As a Thiophilic Or Carbophilic Lementioning
confidence: 99%
“…On the basis of these mechanistic experiments, a role for boron as a carbophilic Lewis acid in this cyclization is proposed, plausibly through an Ad E 2/Ad E 3 mechanism [5,6] (Scheme 2, bottom). Subsequent attack by the sulfur via transition state 13 generates sulfonium intermediate 12.…”
Section: Mechanistic Studies: Boron As a Thiophilic Or Carbophilic Lementioning
confidence: 99%